Photoconductive antennas based on epitaxial films In0.5Ga0.5As on GaAs (1 1 1)A and (1 0 0) substrates with a metamorphic buffer. (22nd May 2018) - Kuznetsov, K A; Galiev, G B; Kitaeva, G Kh; Kornienko, V V; Klimov, E A; Klochkov, A N; Leontyev, A A; Pushkarev, S S; Maltsev, P P
Notice of redundant publication: "Photoconductive antennas based on epitaxial films In0.5 Ga0.5 As on GaAs (1 1 1)A and (1 0 0) substrates with a metamorphic buffer" K A Kuznetsov et al 2018 Laser Physics 28 076206. Since the publication of this article, it has been brought to the attention of the editors that the article was intended for publication in the journal Laser Physics Letters, but was instead published in Laser Physics . This was due to a handling error by IOP Publishing and we apologise to the authors for this error. As such a notice of redundant publication should be applied to this article, and readers are referred to the correct version of the article which can be found in Laser Physics Letters (http://iopscience.iop.org/article/10.1088/1612-202X/aac7bb ). Abstract The terahertz (THz) wave generation by the spiral photoconductive antennas fabricated on the low-temperature and high-temperature grown undoped and Si-doped In0.5 Ga0.5 As films is studied by the terahertz time-domain spectroscopy method. The In0.5 Ga0.5 As layers were grown by molecular beam epitaxy on GaAs substrates with (1 0 0) and (1 1 1)A crystallographic orientations utilizing step-graded In x Ga1− x As metamorphic buffer. The antennas are excited by radiation of Er 3+ -fiber laser at 1.56 μ m wavelength in two regimes: with pulse durations of 2.5 ps or 100 fs. It is found that the THz wave generation is 3–4 times more effective in the case of InGaAs-based antennas on (1 1 1)A GaAs substrates as compared to the (1 0 0) substrates. Power-voltage characteristic of the LT-InGaAs antenna up to and beyond threshold breakdown voltage are reported.